Limits of Molecular Dithienylethene Switches Caused by Ferrocenyl Substitution. Issue 12 (8th March 2016) - Escribano, Alejandra; Steenbock, Torben; Herrmann, Carmen; Heck, Jürgen
Abstract: The efficiency of photochromic switches can be modified by attaching organic or organometallic groups to the photochromic core. We studied ferrocene‐substituted dithienylethene switches differing by the size of the cycloalkene ring bridging the two thiophene groups. The results were compared with their chlorine‐substituted counterparts and an ethynyl‐ferrocene substituted switch published earlier by Guirado and co‐workers. From the measured UV/Vis spectra, both ferrocene‐substituted compounds were found to be considerably less likely to switch than the corresponding chlorine‐substituted ones. Kohn–Sham density functional theory calculations suggested that this is due to a multitude of energetically close‐lying excited states in the former, which may offer multiple pathways for excitation and relaxation, out of which only one leads to ring opening or closing. By contrast, the chlorine‐substituted switches have one energetically more isolated state that is responsible for the switching. The increase in the available excited states in the ferrocene‐substituted switches was attributed to mixing between orbitals from the ferrocene units and the π system of the bridge. Abstract : A snail's pace : Controlling interactions between magnetically or redox‐active subunits is important in the design of functional molecules and molecular materials. Switching such interactions by light has the advantages of fast response and spatiotemporal control. Attaching the active subunits to a switchable bridge can affect the properties of the photoswitches. We study these effects for ferrocenes directly attached to dithienylethene switches.